EFEKTIFITAS FORMULA “SUPROMIN” (MAKANAN ENTERAL DARI TEMPE) TERHADAP PERBAIKAN KADAR ALBUMIN DAN KOLESTEROL PASIEN STROK - Sri Sulistiyaningsih; Budiyanti Wiboworini; Ida Nurwati (PERSATUAN AHLI GIZI INDONESIA, 2022)
Stroke has been a leading cause of death in Indonesia based on Riskesdas data in 2018, it is known that Sroke's prevalence increased from 7 per million to 10.9 per million. Patients with acute stroke were found to be lacking in protein energy by 16.3 percent - 35 percent.